Regulation of lipid droplet (LD) formation in hepatocytes via regulation of SREBP1c by non-coding RNAs - El Sobky, Shereen A.; Aboud, Nourhan K.; El Assaly, Nihal M.; Fawzy, Injie O.; El-Ekiaby, Nada; Abdelaziz, Ahmed I. (Frontiers in Medicine, 2022)
Introduction: Increased de novo lipogenesis (DNL) is one of the contributing factors leading to fat accumulation and Non-alcoholic fatty liver disease (NAFLD). Among the critical transcription factors (TFs) regulating DNL is mTOR and its down-stream lipogenic TF: SREBP1c. In recent years it has been established that non-coding RNAs (ncRNAs) contribute in regulating biological processes as well as to pathogenesis of diseases. Our group had previously characterized a couple of microRNAs that can target and regulate the expression of both mTOR & SREBP1c. Accordingly, this study aimed at extending our understanding about the role of ncRNAs in regulating mTOR/SREBP1c axis in an attempt to understand the role of non-coding transcriptome in DNL and lipid droplet (LD) formation. Hence, the short ncRNA miR-615-5p was chosen as it was proven by our group to target mTOR in HCC as well as the long non-coding RNA (lncRNA) H19 which was also shown in the literature to target mTOR. Methodology: To achieve this aim, a fatty liver cell model was generated by treating Huh7 cells with 800μM oleic acid (OA) to promote LD formation. Transfection of miR-615-5p mimics or H19 over-expression vector in this model was performed followed by measuring the relative quantification of the mRNA of its putative targets: mTOR and SREBP by quantitative real time PCR (qRT-PCR) and measuring the protein levels by western blot. Results: miR-615-5p was able to reduce both targets significantly on the mRNA level & the protein level compared to control cells. To determine the functional impact of miR-615-5p and H19 on LD formation and triglycerides (TG) accumulation, both non-coding RNAs were transfected followed by fixation of cells, and then LDs were stained, imaged and characterized, and TG extraction & quantification. Both mir-615-5p and H19 were able to significantly reduce LD count, total area & TG compared to control cells. Conclusion: To conclude, this study shows for the first time the impact of miR-615-5p and H19 on the mTOR/SREBP1c axis and thus its functional impact on LDs & TG accumulation. These findings might pave the way for using ncRNAs as potential therapeutic targets in the management of fatty liver.